Semiconductor Research Experimental Techniques - Patane, Amalia; Balkan, Naci (Springer Series in Materials Science,, 2012)
The book describes the fundamentals, latest developments and use of key experimental techniques for semiconductor research. It explains the application potential of various analytical methods and discusses the opportunities to apply particular analytical techniques to study novel semiconductor compounds, such as dilute nitride alloys. The emphasis is on the technique rather than on the particular system studied.